Legitimating Multilingual Teacher Identities in the Mainstream Classroom. (January 2017) - Higgins, Christina; Ponte, Eva
Abstract : This article explores the identities of a group of elementary teachers who participated in a professional development (PD) project on multilingual language learners.1 We study how the participating teachers drew on different aspects of their identities to respond to encouragement to increase their attention to students' diverse multilingual repertoires in classroom practices. Drawing on research that has sought to open up more spaces for multilingualism in North American, English‐medium schooling, the teachers were invited to create multilingual print environments (Lotherington, 2013 ), use group work to increase oral participation among multilingual learners, invite students to take on the role of 'language teacher' (Cary, 2008 ), and encourage students to author multilingual identity texts (Cummins & Early, 2010 ). As the teachers grappled with these ideas, we collected data in the form of classroom observation notes, interviews, assignments, and WebCT posts. Using Gee's (2001) framework for identity, our analysis sheds light on how the teachers enacted their professional identities as they worked to put the PD concepts and recommendations into practice. Our analysis reveals how the teachers' own linguistic histories strongly shaped their views about multilingualism in schools, but it also demonstrates that a formally sanctioned opportunity to experiment with multilingual pedagogies opened up new spaces for critical self‐reflection about the links among languages, teachers' identities, and academic engagement for multilingual learners.